Systemic Theorizing: Traversing Between Constructivism and Structural Realism - Dr. Imran Syed; Dr. Lubna Abid Ali (Journal of Political Studies, 2018)
This research paper looks at the constructivist theoretical framework and the systemic level of analysis in International Relations (IR). The paper examines the levels of analysis issue and the evolution of this issue in the light of the great debates in IR. The research provides a description of basic tenants of constructivism, a description of the varieties of constructivist theorizing and a brief account of how the different varieties compare to each other. The research paper then focuses on Alexander Wendt and examines Wendt’s constructivist theoretical framework and particularly how he sees analysis at the systemic level. The issue of structure and agency figures in the debate on levels of analysis and the paper examines this facet of systemic theorizing. The research paper compares how Wendt’s systemic analysis is a departure from the structural realism of Kenneth Waltz. Waltz’s theory was and remains an influential theory of IR and by comparing these two important theories a better understanding is obtained not only of systemic theorizing in the constructivist theoretical framework but also aspects of the systemic level of analysis in IR in general.